«Քյոռօղլի» էպոսի պատմական հենքը և XVII-XVIII դդ. հայերեն ժամանակագրությունները - Ռամազյան, Սամվել («Նաիրի» հրատ.)
The historical basis of the epic of Koroglu is generally related to the Jelali (Celali) Rebellions, which took place in the Ottoman Empire in the late 16th and early 17th centuries. Relying on a centuries-old well-established tradition, the Armenian historiography of the 17th-18th centuries preserved important and unique information about the Jelali Rebellions and the Jelali leaders, the historical prototypes of the characters of the epic: Koroglu, Kiziroglu Mustafa, Kosa Safar and others. Particularly important for the study of the historical background of the epic are not only the works of 17th century Armenian historians Arakel Davrizhetsi (Arakel of Tabriz), Grigor Daranaghtsi (Kamakhetsi) and Eremia Komurjian, but also “minor chronicles” of the same period. These sources contain information about the characters of the epic, as well as certain historical events that transpire in the epic. Историческую основу эпоса “Кероглы” в целом составляют джелалийские восстания в Османской империи в конце XVI – начале XVII вв. Опираясь на многовековую стабильную традицию, армянская историография XVII-XVIII вв. сохранила важные и уникальные сведения об этих исторических событиях, в том числе о предводителях джелали, исторических прототипах действующих лиц эпоса: Кероглы, Гзироглы Мустафе, Коса Сафаре и др. Особенную важность для изучения исторических предпосылок эпоса представляют не только труды армянских историков XVII в. Аракела Даврижеци, Григора Даранагци (Камахеци) и Еремии Кеомурчяна, но также “малые хроники” того же периода. Данные армянские источники содержат сведения как о персонажах эпоса, так и о некоторых отраженных в нем исторических событиях.
Keywords: Աղբյուրագիտություն; Բանահյուսություն